The International Labour Organization - Maul, Daniel (De Gruyter, 2020)
This is the first comprehensive account of the International Labour Organization's (100 year-long) history. The Centenary publication shows the ILO as a forum and an actor in the area of Global Social Policy. It opens a perspective on the manifold ways the ILO over a hundred years sought to structure debates on social policy across national borders and render practical contributions for the world of work and the area of social policy at large.